(untitled) (Research, Society and Development, 2022)
Health promotion is considered an important strategy for the dissemination of healthy habits, as they promote an improvement in the population’s quality of life, thus avoiding exposure to conditioning factors for certain diseases. Given this, the work aimed to collaborate with the pedagogical practice based on the critical-reflexive conception and the active participation of the students, focusing on the promotion of healthy eating. The practice was applied to an 8th grade elementary school class from a state school in Arapiraca, AL, in which it was divided into three moments. After applying the questionnaire, a lecture on the constitution and classification of foods and practical activities related to healthy eating and food pyramid was offered. The results of the work were satisfactory, as most students actively participated in the activities and in a very interesting way. It could be inferred from the application of this activity that the 8th grade students, to whom the practice was directed, could understand about the constitution of foods and what are the food groups that make up the food pyramid. The application of practical activities was very important to sensitize students to obtain good eating habits, so as to have a healthier life.